A Hand‐Held Ultrasound Device for the Assessment of Peripheral Nerves in Leprosy. Issue 1 (11th November 2020) - Wheat, Stephen W.; Stryjewska, Barbara; Cartwright, Michael S.
ABSTRACT: BACKGROUND AND PURPOSE: Mycobacterium leprae complex affects peripheral nerves, causing nerve enlargement. This proof‐of‐concept pilot study was conducted to determine if a small hand‐held ultrasound device can accurately identify nerve involvement in individuals with leprosy. METHODS: Peripheral nerve ultrasound was conducted of the bilateral median (wrist, forearm, elbow, and mid‐humerus), ulnar (wrist, forearm, elbow, 4 cm proximal to the elbow, and mid‐humerus), C5 root, and greater auricular nerves with a standard ultrasound device (15 Mhz) and a hand‐held ultrasound device (5 MHz). Nerve cross‐sectional areas were compared using the two devices. RESULTS: Eight individuals with leprosy were examined. Strong correlation was found between the standard and hand‐held ultrasound devices ( r = .76, P < .001). A certain amount of variability between ultrasound devices may occur for multiple reasons. CONCLUSION: A hand‐held ultrasound device can readily identify nerve enlargement in individuals with leprosy. This type of device may assist in the diagnosis of leprosy in areas with limited healthcare resources because of the portability and low‐cost nature of such devices.